FETAL OUTCOME IN PREGNANT WOMEN WITH BODY MASS INDEX MORE THAN 25. - Aasma Naz1, Muthira Yasin2, Anila Tahzeen3, Raishem Ali Baloach4, Sakina Mahar5, Kiran Aamir Akhund6., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
BACKGROUND: When there is a sudden miscarriage that is the most widely recognized intricacy of pregnancy cause the imperishable anxiety in couple which are mentally prepared for a child. OBJECTIVE: The objectives were to determine the maternal and neonatal outcome after previous spontaneous abortion. METHODOLOGY: A six month Cross sectional study was done at the Department of Obstetrics and gynaecology department of Peoples Medical University & Hospital Nawabshah during the time period of 1st January 2018 to 30th juine 2018. A total of 246 women with history of spontaneous abortion were included in this study. Detailed History was taken from all the patients with special regard to spontaneous abortions. All of the patients entered the study during the first trimester and was followed until delivery. All the record was entered into Proforma. RESULTS: The average age of the women was 25.90±4.51 years. Maternal morbidity like premature rupture of membrane 11.8%, antepartum hemorrhage 8.5%, recurrence abortion 5.3%, intrauterine fetal death 5.3%, cesarean delivery 66.7%, instrumental delivery 10.2%, placenta previa 8.9%, preeclampsia 7.7% and eclampsia was observed in 6.1% women. Regarding neonatal outcome, there were 37% low birth weight (<2.5), 4.1% gross congenital anomaly, 40.2% low apgar score (≤6), 4.1% breech presentation, 46.7% preterm delivery, 44.3% NICU Admission and 2% perinatal mortality. CONCLUSION: from this study it is concluded that the future pregnancy is always at higher risk if woman has previous unsuccessful past obstetric history so prenatal care is needed in future.